THE USE OF STUDENTS’ TEAM ACHIEVEMENT DIVISION IN TEACHING WRITING RECOUNT TEXT - Fitri Ruska, Nanda Dwi; ., Regina; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract : The research was conducted at the eighth grade students of SMP Negeri 6 Pontianak in academic year 2016/2017. This research aimed to investigate whether or not the use of Students Team Achievement Division in teaching writing recount text affects the students’writing ability significantly. The method of the research was a pre experimental research with one group pre-test - post-test design. The population of the research was 242 eighth grade students of SMP Negeri 6 Pontianak. The sample of the research was class VIIIA which consisted of 33 students which was taken by using clustering sampling. The data was collected by using measurement technique. The researcher provided the written test as the tool of data collecting on the research. The mean score of the students’ pre-test was 36.75 and the mean score of students’ post-test was 60.2. Based on the computation, the result of the Effect Size (ES) was 1.58. The effectiveness of the use of Students’ Team Achievement Division (STAD) in teaching writing recount text was strong. It was showed that the use of Students’ Team Achievement Division in teaching writing recount text was highly effective. The alternative hypothesis of the research was accepted. Keywords : Teaching Writing, Students’ Team Achievement Division, Recount  Text. Abstrak : Penelitian ini dilakukan pada siswa kelas VIII dari SMPN 06 Pontianak tahun ajaran 2016/2017. Tujuan dari penelitian ini adalah untuk mencari tahu apakah penggunaan Students’ Team Achievement Division (STAD) dalam pengajaran menulis teks recount bisa berdampak secara signifikan terhadap kemampuan siswa dalam menulis. Metode yang digunakan oleh penelitian ini  adalah pre-experimental dengan rancangan satu grup pre-test - post-test. Populasi penelitian ini berjumlah 242 siswa kelas VIII SMPN 06 Pontianak. Sample penelitian ini adalah siswa kelas VIIIA yang terdiri dari 33 siswa yang diambil menggunakan teknik clustering sampling. Pengumpulan data diperoleh dengan menggunakan teknik pengukuran. Peneliti memberikan  tes menulis sebagai alat untuk mengumpulkan  data penelitian ini. Nilai rata-rata pre-test yang diperoleh adalah 36,75 dan nilai rata-rata pada post-test adalah 60,2. Berdasarkan perhitungan, hasil Effect Size (ES) adalah 1,58. Efektivitas dari penggunaan Students’ Team Achievement Division (STAD) dalam pengajaran menulis teks recount adalah sangat kuat. Itu menunjukkan bahwa penggunaan Students’ Team Achievement Division (STAD) dalam pengajaran menulis teks recount sangat efektif. Hipotesis alternatif penelitian diterima. Kata kunci : Pengajaran Menulis, Students’ Team Achievement Division, Teks Recount.